Community Preparedness in Facing Mount Semeru Eruption to Support National Security - Dimas Raka Kurniawan Putra; Syamsul Maarif; Lilik Kurniawan (CV. AFDIFAL MAJU BERKAH, 2023)
The change in national security paradigm has turned into security sector reform. This change causes that national security does not only focus on territorial security but also focuses on human security. One of the factors that can disturb human security is disaster. The community's lack of preparedness for the eruption of Mount Semeru means that the community is still at high risk, causing 64 people to die. This study aims to analyze community preparedness in facing the eruption of Mount Semeru in order to support national security. This research method uses a qualitative research approach with a descriptive approach. The data analysis technique uses the qualitative data analysis technique belonging to Miles, Hubermen and Saldana. The results of this study are as follows: 1) In terms of the preparation of temporary evacuation sites, fulfillment of basic needs, and preparation of restoration of facilities and infrastructure have been carried out well while the preparation of RPKB, early warning systems, training and simulations, and preparation of accurate data is still not well executed; 2) Efforts made by the government and stakeholders in increasing community preparedness for an effective response and building better have been carried out well through training in Disaster Resilient Villages, Disaster Safe Education Unit, making the Jaga Semeru application and creating a Whatsapp Group which makes the community have preparedness better in dealing with the eruption of Mount Semeru. If the government and stakeholders make efforts to increase preparedness, the community will have an effective response and build back better.